Research progress on vestibular dysfunction and visual–spatial cognition in patients with Alzheimer’s disease - Huang, Yan; Xu, Jiaxi; Zhang, Xuehao; Liu, Yuhe; Yu, Enyan (Frontiers in Aging Neuroscience, 2023)
Alzheimer’s disease (AD) or vestibular dysfunction may impair visual–spatial cognitive function. Recent studies have shown that vestibular dysfunction is increasingly common in patients with AD, and patients with AD with vestibular impairment show more visual–spatial cognitive impairment. By exploring the relationship and interaction mechanism among the vestibular system, visual–spatial cognitive ability, and AD, this study aims to provide new insights for the screening, diagnosis, and rehabilitation intervention of patients with AD. In contrast, routine vestibular function tests are particularly important for understanding the vestibular function of patients with AD. The efficacy of vestibular function test as a tool for the early screening of patients with AD must also be further studied. Through the visual–spatial cognitive ability test, the “spatial impairment” subtype of patients with AD, which may be significant in caring for patients with AD to prevent loss and falls, can also be determined. Additionally, the visual–spatial cognitive ability test has great benefits in preventing and alleviating cognitive decline of patients with AD.